Metabolite Profiling in Anticancer Drug Development: A Systematic Review - Muhamad N; Na-Bangchang K (Dove Medical Press, 2020)
Nadda Muhamad,1 Kesara Na-Bangchang1– 3 1Chulabhorn International College of Medicine, Thammasat University, Pathum Thani 12120, Thailand; 2Center of Excellence in Pharmacology and Molecular Biology of Malaria and Cholangiocarcinoma, Chulabhorn International College of Medicine, Thammasat University, Pathum Thani 12120, Thailand; 3Drug Discovery and Development Center, Office of Advanced Sciences and Technology, Thammasat University, Pathum Thani 12120, ThailandCorrespondence: Kesara Na-BangchangChulabhorn International College of Medicine, Thammasat University (Rangsit Center), 99 Moo 18, Paholyothin Road, Klongnung, Klongluang, Pathum Thani 12120, ThailandTel +66 2 564 4400 ext 1800Fax +66 2 564 4398Email kesaratmu@yahoo.comAbstract: Drug metabolism is one of the most important pharmacokinetic processes and plays an important role during the stage of drug development. The metabolite profile investigation is important as the metabolites generated could be beneficial for therapy or leading to serious toxicity. This systematic review aims to summarize the research articles relating to the metabolite profile investigation of conventional drugs and herb-derived compounds for cancer chemotherapy, to examine factors influencing metabolite profiling of these drugs/compounds, and to determine the relationship between therapeutic efficacy and toxicity of their metabolites. The literature search was performed through PubMed and ScienceDirect databases up to January 2019. Out of 830 published articles, 78 articles were included in the analysis based on pre-defined inclusion and exclusion criteria. Both phase I and II enzymes metabolize the anticancer agents/herb-derived compounds . The major phase I reactions include oxidation/hydroxylation and hydrolysis, while the major phase II reactions are glucuronidation, methylation, and sulfation. Four main factors were found to influence metabolite formation, including species, gender, and route and dose of drug administration. Some metabolites were identified as active or toxic metabolites. This information is critical for cancer chemotherapy and anticancer drug development.Keywords: metabolism, metabolite profile, anticancer, herbal medicine, cancer